Relationship of Postburn Intervals to the Incidence and Success of Bobwhite Nesting in Southwest Georgia - Ronald C. Simpson (National Quail Symposium Proceedings, 2017)
Data relating to the interval between the last prescribed burn and current nesting attempts were collected from 842 nests known to have contained eggs during the 1969-71 nesting seasons on a 1,262-acre area in southwest Georgia. The yearly habitat acreage per nest averaged 11.4 acres on areas burned during the current spring, 1.4 acres on areas 1 yr postburn, 2.3 acres on areas 2 yr postburn, and 1.8 acres on areas more than 2 yr postburn. One successful nest occurred per 32.0 acres on burned areas, 9.2 acres on areas 1 yr postburn, 14.5 acres on areas 2 yr postburn, and 38.0 acres on areas more than 2 yr postburn. Initiation dates were known for 385 of the 842 nests. The occurrence of nests on burned areas was low prior to June 16. Nests on burned areas increased after June 15 (1 nest/30.1 acres/year) but the incidence was still lower than that on unburned areas (1 nest/11.1 acres/year). Data indicate that areas burned during the current spring are used by quail for nesting, but that maintenance of suitable cover conditions 1 and 2 yr postburn is the greatest benefit to nesting derived from prescribed burning.